Penerapan Program Zero Accident K3 melalui Metode Penyuluhan Keselamatan dan Kesehatan Kerja di Mesin Industri Kecil (UKM) Wilayah X - berlian yuli saputri; ketjuk herminaju; ria anggraini; dewi zuniawati (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2024)
Community service activities are one form of the Tri Dharma of Higher Education which must be carried out by lecturers. Community service activities use a training concept, apart from being given a theoretical explanation, participants are also provided with examples of the application of K3 standards in the work environment which are shown visually as well as practical handling of dangers that threaten K3. The results of this activity include, among other things, participants being more aware of the threat of danger in the workplace, being able to protect and maintain K3 so that performance can increase, ensuring production sources are well maintained. In general, training activities provide knowledge in the zero accident program to employees in implementing K3, it is hoped that it will raise their enthusiasm to apply it in the workplace later so that zero accidents are achieved.